Comparison of next‐generation portable pollution monitors to measure exposure to PM2.5 from household air pollution in Puno, Peru. (23rd January 2020) - Burrowes, Vanessa J.; Piedrahita, Ricardo; Pillarisetti, Ajay; Underhill, Lindsay J.; Fandiño‐Del‐Rio, Magdalena; Johnson, Michael; Kephart, Josiah L.; Hartinger, Stella M.; Steenland, Kyle; Naeher, Luke; Kearns, Katie; Peel, Jennifer L.; et al.
Abstract: Assessment of personal exposure to PM2.5 is critical for understanding intervention effectiveness and exposure‐response relationships in household air pollution studies. In this pilot study, we compared PM2.5 concentrations obtained from two next‐generation personal exposure monitors (the Enhanced Children MicroPEM or ECM; and the Ultrasonic Personal Air Sampler or UPAS) to those obtained with a traditional Triplex Cyclone and SKC Air Pump (a gravimetric cyclone/pump sampler). We co‐located cyclone/pumps with an ECM and UPAS to obtain 24‐hour kitchen concentrations and personal exposure measurements. We measured Spearmen correlations and evaluated agreement using the Bland‐Altman method. We obtained 215 filters from 72 ECM and 71 UPAS co‐locations. Overall, the ECM and the UPAS had similar correlation (ECM ρ = 0.91 vs UPAS ρ = 0.88) and agreement (ECM mean difference of 121.7 µg/m 3 vs UPAS mean difference of 93.9 µg/m 3 ) with overlapping confidence intervals when compared against the cyclone/pump. When adjusted for the limit of detection, agreement between the devices and the cyclone/pump was also similar for all samples (ECM mean difference of 68.8 µg/m 3 vs UPAS mean difference of 65.4 µg/m 3 ) and personal exposure samples (ECM mean difference of −3.8 µg/m 3 vs UPAS mean difference of −12.9 µg/m 3 ). Both the ECM and UPAS produced comparable measurements when compared against a cyclone/pump setup.